LIPID PEROXIDATION SYSTEM AND ANTIOXIDANT DEFENCE STATE IN PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS SEVERITY STAGES I-II COMBINED WITH PARASITOSES - Savel'eva, Natal'ya (Journal of Education, Health and Sport, 2015)
The article presents the results of research on the state of lipid peroxidation and antioxidant defense in patients with chronic generalized periodontitis (CGP) severity stages I-II combined, with parasitoses. The aim of the study was to investigate lipid peroxidation and antioxidant defense in patients with chronic generalized periodontitis (CGP) severity stages I-II with parasitoses (enterobiasis, toxocariasis, giardiasis). The study was conducted on 540 patients with chronic generalized periodontitis severity stages I-II combined with parasitic invasion on the background (the main groups). The comparison group consisted of 90 patients with CGP severity stages I-II without a parasitic invasion. The control group consisted of 30 patients without periodontal disease and chronic diseases of other organs and systems, who were considered relatively healthy during the study period. To evaluate the intensity of free radical oxidation a screening method of induced blood serum chemiluminescence was used. Catalase activity was determined spectrophotometrically by the decrease of hydrogen peroxide quantity in the medium and superoxide dismutase (SOD) activity was determined in the test with nitroblue tetrazolium. Statistical analysis of the materials was conducted using the methods of mathematical statistics for the analysis of the obtained data. It was found that as the disease progresses and CGP severity stage I changes into severity stage II, lipid peroxidation processes intensify in blood serum and tissues of the body. So, there was a significant increase in the content of lipid peroxidation products: diene conjugates (DC) in groups of patients with parasitoses as compared with the control group - in CGP severity stage I DC content was higher by 30-33%, in CGP severity stage II DC content was higher by 40-41%; in CGP severity stage I triene conjugates (TC) content was higher by 22-24%, in CGP severity stage II triene conjugates (TC) content was higher by 26-27%; content of lipid peroxidation (LP) end products — polymeric fluorescent Schiff bases (SB) — in CGP severity stage I was higher by 34-36%, in CGP severity stage II was higher by 45-47%. Also, in comparison with the control group a significant decrease in the activity of superoxide dismutase (SOD) was observed in patients with parasitoses: in CGP severity stage I it decreased by 20-23%, in CGP severity stage II by 23-26%. However, in patients of the main groups catalase content reduction was recorded: in CGP severity stage I by 22-24%, in CGP severity stage II by 26-27%. It is noted that between patients with CGP severity stages I-II with parasitoses and CGP patients without parasitoses significant differences were determined only in catalase and superoxide dismutase activity, indicating a more severe antioxidant defense disturbance in patients with parasitoses.